Realizing poly(ethylene oxide) as a polymer for solid electrolytes in high voltage lithium batteries via simple modification of the cell setup. Issue 10 (13th April 2021) - Stolz, Lukas; Homann, Gerrit; Winter, Martin; Kasnatscheew, Johannes
Abstract : Cell failure of polymer electrolytes is rather the result of short circuits instead of assumed electrolyte oxidation. A spacer with a constant and defined distance can avoid this failure, thus realize a benchmark system for a more systematic R&D. Abstract : Pure, i.e., linear poly(ethylene oxide)-based solid polymer electrolyte (PEO-based SPE) as a common benchmark system for Li metal batteries (LMBs) is frequently assumed to be unsuitable for high voltage applications e.g., with LiNi0.6 Mn0.2 Co0.2 O2 (NMC622)-based cathodes. In fact, a destructive failure appears immediately after cell operation, seen by a random-like "voltage noise" during charge, rendering continuous charge/discharge cycling in e.g., NMC622||Li cells not possible. Counterintuitively, this failure is a result of short-circuits in the course of e.g., Li dendrite penetration. It is shown that the distance between the electrodes plays a crucial role. This failure is more likely with a lower distance, particularly when the SPE is mechanically prone to shrinkage, for example at higher temperatures as systematically revealed by mechanical compression tests. Additionally, the active mass loading has a crucial impact on short circuits, and thus the "voltage noise" failure, as well. An effective and practically simple solution to realize cell operation with a PEO-based SPE is the incorporation of a spacer between the electrodes. This modification prevents the detrimental shrinkage and enables charge/discharge cycling performance in NMC622||Li cells with a defined and constant electrode distance, thus without voltage noise, and finally fulfills a reasonable benchmark for systematic R&D with specific capacities above 150 mA h g −1 even at 40 °C.